Gambaran Pengguna NAPZA Di Pondok Pesantren Rehabilitasi Suryalaya Inabah XIX Surabaya Penelitian Cross Sectional - Muflih, ,- (2008)
Malfunction of drugs uses is a function drugs without doctor knowingly and supervision. Rehabilitation is one of action which curing and reconditioning drugs users to physical, psychologies, social and spiritual healthy. This research aimed to analyze the description of drugs user and the description of rehabilitation program in lnabah XIX. Design cross sectional in this research was used. Population was used as object it is drugs users who treated rehabilitation in Rehabilitation Pesantren Boarding House Suryalaya Inabah XIX Surabaya with accident sampling are used for defining the sample. So that achieved 16 peoples sample. Independent variable was measured are internal factors; knowledge, value, perception, attitude, age, addicting grade, and compliance. External factors are family supporting, social supporting, economic grade, cost, equipment, activity characteristic, role of institution, and human resources development (SDM) officer. Dependent variable is the description of rehabilitation program in Inabah XIX. Collecting data was done gift demography questionnaire and middle regularly interviewed. Data of this research was calculated by content analysis used. The result of this research describe knowledge was influenced by age, gender, lives, and education level. Value is one of factor have influenced. Drugs users not only have willing about rehabilitation but also have hard conviction to recover of their addicted. Respondent's perception about method was used is good, but their perception of schedule program was bored so that they feel lazy to follow rehabilitation program. All of drugs addicted want to do good attitude, awareness of less or more rehabilitation program, and willing to recommend others is well. Average age of drugs user was treated rehabilitation program about 21-30 years old. It have high addicted can make them feel lazy to follow rehabilitation program. Half of amount respondent told that have good relation with their family. Almost all of respondent get social supporting and feel comfortable during rehabilitation program. Economic is one factor closed with cost. All of respondent told that their cost was recovered by their parent and they feel satisfied about facilities have already exist. Characteristic factor activity important influence drugs user was bored. It can make them compliances in rehabilitation program based on the role was defined. Almost drugs user eventually feel ordinary about the role have already exist, the most important are its pray and dzikir was done based on the role. Almost of respondent's opinion to builder/teacher/lecture of program is positive. In this research almost respondent have been ever didn't follow obligation program like jama'ah pray/pray together, in other hand they feel better condition after follow this program. The main factor was most influenced than others for rehabilitating that happened drugs user in lnabah are characteristic program, role of institution, cost, perception of large population, laziness, and addicted level. So that recreation program is needed to make lost laziness from human resources development (SDM) officer, improvement of discipline, understanding of the role, and formed of character program that all of them for make better drugs user and to optimal the cost was used.